The Importance of Implementing Marketing Strategies for Online Food Business Advantages in Nabire - Camelia Praestuti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The development of online business is growing day by day. Online businesses are everywhere in offering several products that become consumer needs, this has an impact on Papua. This Online Business is not only using the Online Business web with paid domains and hosting, but also many who use social media facilities such as Facebook, Twitter, Whatshap, and there are still many routes that are used to sell. Research Objectives To find out how the marketing strategy implementation model is used so that Online Food business excellence can be achieved in Nabire in addition to knowing how to implement Marketing Strategy towards Online Food Business excellence in Nabire and find out the factors that influence the implementation of marketing strategies on business excellence. Online Food in Nabire. The method used in this study using descriptive research methods. The results of the study show that the implementation of marketing strategies, online business people in offering food products sold online in the city of nabire, is much more dominant and easier to introduce the types and kinds of food products so that consumers can easily reach existing needs.